In Vitro Fertilization, Second Edition. - Elder, Kay (Cambridge University Press, 2003)
This comprehensively updated and substantially expanded new edition builds on its successful and popular predecessor, whilst retaining the practical features which made the first edition such an essential guide to IVF. This new edition distils a wealth of practical and scientific detail for the benefit of all IVF practitioners.